Language policy and identity politics in the United States - Schmidt, Ronald, 1943- (Temple University Press, 2000)
An engaging discussion about the use of English and other languages in the United States.
Keywords: Language policy -- United States.; Americanization.; Cultural pluralism -- United States.; Politique linguistique -- États-Unis.; Américanisation.; Diversité culturelle -- États-Unis.; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Sociolinguistics.; SOCIAL SCIENCE -- General.; Americanization; Cultural pluralism; Language policy; United States; Mehrsprachigkeit; Sprachpolitik; USA; Amerikanisches Englisch.